Evaluation of Indoor Bacterial Load and Its Association with Respiratory Symptoms among Children in Kuantan Early Childhood Centres - Mohamad Fandi, Noor Fatihah; Mohammad Maliki, Nur Aliya Maisarah; Mohamad Zaky, Nurul Falah; Alias, Norsyuhada; Zahaba, Maryam; Sopian, Nor Ashikin (International Journal of Allied Health Sciences, 2025)
Background: Indoor Air Quality (IAQ) plays a crucial role in ensuring a healthy and comfortable environment, particularly in early childhood education centers (ECEs). Children are especially vulnerable to poor IAQ due to their developing immune and respiratory systems. This study investigated the indoor bacterial load and the associated respiratory symptoms among children in selected ECEs in Kuantan. Methods: A cross-sectional study design was conducted to assess indoor bacterial counts and physical parameters (temperature, relative humidity, and wind speed), which were measured with the Surface Air System SAS IAQ 100 and the Testo Air Meter 440, respectively. Potential respiratory symptoms (cough, wheezing, phlegm, and breathlessness) were evaluated in 30 children using a parent-administered questionnaire adopted from the American Thoracic Society and previous studies. Results: Both ECEs recorded total bacterial counts exceeding the Industry Code of Practice (ICOP) limit, with concentrations of 617.22 CFU/m3 and 647.22 CFU/m3, respectively. The recorded temperatures (27.41? and 27.96?) also surpassed the ICOP comfort range. Among the children, cough was the most commonly reported symptom (23.3%), followed by wheezing (16.7%), and phlegm (10.0%). No cases of breathlessness symptoms were reported in children. Statistical analysis indicated no significant association between the indoor bacterial load and the respiratory symptoms observed. The study was limited by the small sample size and the short monitoring duration, which may not fully represent variations in bacterial levels across different times or seasons. Additionally, the high bacterial counts observed might have been influenced by occupant density, cleaning practices, and ventilation patterns, which were not controlled in this study. Conclusion: Overall, the findings highlight the need for improved cleanliness and ventilation practices in indoor spaces of ECEs to enhance IAQ and promote children’s health and well-being.